A novel Mn-containing conducting metallopolymer obtained by electropolymerization in aqueous solution of a tetranuclear oxo-bridged manganese complex - Martin, Cibely S. [UNESP]; Teixeira, Marcos F. S. [UNESP] (Royal Soc Chemistry, 2011)
The [Mn(4)(IV)O(5)(terpy)(4)(H(2)O)(2)](6+) complex shows great potential for electrode modification by electropolymerization using cyclic voltammetry. The electropolymerization mechanism was based on the electron transfer between dx(2)-y(2) orbitals of the metallic center and p pi orbital of the ligand.